2011
DOI: 10.1038/nmeth.1585
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Fourier-transform infrared chemical imaging with multiple synchrotron beams

Abstract: Conventional Fourier-transform infrared (FTIR) microspectroscopic systems are limited by an inevitable trade-off between spatial resolution, acquisition time, signal-to-noise ratio (SNR) and sample coverage. We present an FTIR imaging approach that substantially extends current capabilities by combining multiple synchrotron beams with wide-field detection. This advance allows truly diffraction-limited high-resolution imaging over the entire mid-infrared spectrum with high chemical sensitivity and fast acquisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
315
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(319 citation statements)
references
References 36 publications
3
315
0
Order By: Relevance
“…The deconvolution algorithm was tested on several different test samples (tissue, polystyrene beads). These tests confirmed that the spatially deconvolved spectra preserved the original spectral features [102]. In cases where the PSF is only poorly determined, or entirely unknown deconvolution can be performed also using an estimate of the point spread function.…”
Section: Deconvolution In Vibrational Hyperspectral Imagingsupporting
confidence: 53%
See 2 more Smart Citations
“…The deconvolution algorithm was tested on several different test samples (tissue, polystyrene beads). These tests confirmed that the spatially deconvolved spectra preserved the original spectral features [102]. In cases where the PSF is only poorly determined, or entirely unknown deconvolution can be performed also using an estimate of the point spread function.…”
Section: Deconvolution In Vibrational Hyperspectral Imagingsupporting
confidence: 53%
“…recently presented a de-blurring method for FT-IR hyperspectral imaging matrices in which deconvolution was carried out by the help of the instrument-specific PSF [102]. The suggested deconvolution technique relied on the knowledge of the wavelength-dependent PSF: this function was determined experimentally by MIR transmittance measurements of a 2 µm pinhole [102]. To avoid the introduction of additional noise, the pinhole data were fitted using the diffraction pattern of a Schwarzschild objective as the fit model [102,103].…”
Section: Deconvolution In Vibrational Hyperspectral Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22][23][24] However, spatial resolution in transmission mode is lower than that of micro-ATR mode even when measured using a powerful synchrotron source. [25][26] Although a recent report 27 has shown that, by using a multi-beam synchrotron source and a high magnifying power objective, the spatial resolution in transmission mode can approach that of micro-ATR mode.…”
Section: Introductionmentioning
confidence: 99%
“…Done correctly, this should reduce the pixel-to-pixel illumination difference dramatically, removing the artifacts across IR images. We will finally be able to exploit the order of magnitude spectral advantage in signalto-noise expected per single FPA pixel at the highest magnification and image oversampling [8,9]. Currently under commissioning, the aim is to take users with this system within the next year.…”
Section: Technical Reportsmentioning
confidence: 99%